Increased Intracranial Pressure Due to Chronic Active Epstein-Barr Virus Infection - Daǧdemir, A.; Taşdemir, H.A.; Dilber, C.; Gök, F.; Kubar, A. (Elsevier Science Inc, 2006)
Central nervous system involvement in Epstein-Barr virus infection usually presents as meningitis, encephalitis, or encephalomyelitis, mostly in the acute form of the disease. In chronic active infection, the clinical situation may also resemble acute infection as well findings of chronic inflammation such as calcification. This report presents an 8-year-old female with chronic active Epstein-Barr virus infection and encephalitis complicated by increased intracranial pressure who was managed with repeated lumbar punctures and medical treatment including anti-edema and antiviral therapies. © 2006 Elsevier Inc. All rights reserved.